La Ley de Separación de 1905: luces y sombras en la génesis de la idea de laicidad en Francia = The French Law of Separation of 1905 : perspectives on the genesis of the idea of "laïcité" in France - Torres Gutiérrez, Alejandro (Anuario de historia de la Iglesia, 2016)
This paper analyzes critically how the French Law of Separation of 1905 came into being, explaining its social context, its main contents, and especially, the meaning and scope of the so-called associations of cult , and the end of public financial support for recognized religious cults established in Napoleonic times. It describes its reception by the Church, the crisis in the relations between Church and State, and the long march towards the resolution of this problem, through the adoption of the new category of diocesan associations . We reflect on the traumatic genesis of the idea of laïcité , and how this affected changes in legislation, whose consequences are still in force.